Navigating Information Overload pada Mahasiswa Non-Library and Information Science dalam Pencarian Informasi Akademik - Cahyaningtyas, Dwi Fitrina; Maulida Zakiah, Diana (Perpustakaan Universitas Gadjah Mada, 2025)
The development of information technology has drastically changed the way students access and utilize academic content. Searching for information has become much easier thanks to the availability of various digital platforms. However, this convenience also poses new challenges, one of which is information overload. Students, especially those not from Library and Information Science programs (non- Library and Information Science), often find it challenging to assess and select relevant and reliable sources. This is due to their low information literacy skills. This study aims to explore the experiences of non-Library Information Science students in dealing with information overload when searching for academic information. This study uses a qualitative descriptive approach. Data were collected through in-depth interviews with four non-Library Information Science students who were selected purposively. The results show that non-Library Information Science students experience information overload due to their limited information literacy skills. They struggle to distinguish credible academic sources, despite generally relying heavily on Google and artificial intelligence-based tools in their information search. Cross-disciplinary information literacy training is essential for enabling students to critically evaluate information and maintain academic integrity in the digital age. Keywords: Academic Information Seeking; Information Seeking Behavior; Information overload, LIS Studies; Information Literacy